Towards modulating the colour hues of isoindigo-based electrochromic polymers through variation of thiophene-based donor groups. Issue 7 (20th January 2022) - Chua, Ming Hui; Toh, Sheng Heng Gerald; Ong, Pin Jin; Png, Zhuang Mao; Zhu, Qiang; Xiong, Shanxin; Xu, Jianwei
Abstract : This paper demonstrated that the hues of both neutral and oxidised colours of isoindigo-based donor–acceptor polymers could be tuned subtly by means of variation of the number and type of donor groups. Abstract : Conjugated polymers containing isoindigo electron acceptor groups have gained attention for electrochromic (EC) applications in recent years. To obtain a deeper fundamental understanding of the EC properties of isoindigo-based conjugated polymers, a series of six isoindigo-based donor–acceptor alternating conjugated polymers containing thiophene, thieno[3, 2- b ]thiophene and 3, 4-ethylenedioxythiophene (EDOT) donor units were synthesized, and their EC properties were studied. All six polymers revealed cyan green colours in the neutral states and bluish-grey colours in the oxidised states. Colourimetric studies (CIE 1976 L * a * b * colour space) showed that negative a * and b * values of the polymers in the neutral state converged towards the true black position of a *, b * = 0 upon electro-oxidation. An increase in transmissivity as evidenced by an increase in L * values was also observed. Notably, it was found that the hues of both neutral and oxidised colours could be tuned through variation of the numbers and types of donor groups. Furthermore, high colouration efficiency of up 626 cm 2 C −1, which is by far the highest amongst all reported isoindigo-based EC polymers, can be achieved in the case of thieno[3, 2- b ]thiophene as a donor. The structure–property relationships in other EC switching properties such as optical contrasts, switching speeds and switching stabilities were also studied. These findings are believed to be useful towards the future development of better-performing EC polymers based on the isoindigo acceptor and the relevant colour tuning strategies.